PERAN MEDIA SOSIAL TIKTOK DALAM MENINGKATKAN KUALITAS DAN JANGKAUAN DAKWAH ISLAM - Adam, Indra (Program Studi Manajemen Dakwah Fakultas Ushuluddin Adab dan Dakwah IAIN Manado, 2025)
The rapid advancement of digital technology requires Islamic preachers (da’i), both those with established scholarly authority and younger generations, to adapt to contemporary developments. Social media, particularly TikTok, has emerged as a strategic platform for disseminating Islamic preaching (da’wah) widely and efficiently. The use of TikTok for da’wah purposes should be guided by an understanding of Islamic jurisprudential principles, especially regarding the objectives of media utilization, to ensure that the content promotes public benefit and avoids negative impacts on individuals and society. This study aims to examine the role of TikTok in enhancing the quality and reach of Islamic da’wah. Using a qualitative approach, the research analyzes da’wah content and interaction patterns between preachers and viewers. The findings indicate that TikTok plays a significant role in expanding the reach of Islamic da’wah and improving the quality of religious messages through creative, interactive, and aesthetically appealing content. Active engagement between da’i and audiences, particularly in responding to viewers’ questions and concerns, contributes to improved religious understanding and positive reciprocal relationships. Furthermore, visually attractive presentations and compelling narratives increase audience engagement, repeated visits, and content sharing, thereby strengthening the effectiveness of digital Islamic preaching.